The influence of institutions on market inefficiency the case of generic drugs - Štěpánek, Martin; Smrčka, Luboš; Strouhal, Jiří, 1980-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
There is a strong evidence suggesting that the law of one price is violated in the retail markets for generic medicaments although the products are essentially homogeneous; the original brand medicaments seem to be sold at a significant price premium over their generic equivalents and also the generics are not sold at the same price. I utilize the standard models of oligopoly and augment them by additional specifications to account for market imperfections and specifications of pharmaceutical industry to explain the dispersed price equilibrium as a natural result of imperfect competition on the market. I argue that under the assumptions of information asymmetry, uncertainty, heterogeneity of patients, and inability to promote products, firms are able to price their medicaments above others. Further, I support my theoretical results with empirical data of medicines sold in the Czech Republic. The observations closely match my conclusions and findings in the prior literature.
Vedoucí práce: Luboš Smrčka
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor bakal. práce]; bakalářské práce; bachelor's theses